Parallel Computation in Uncompressed Digital Images Using Computer Unified Device Architecture and Open Computing Language - Koprawi, Muhammad (LPPM Universitas Islam 45 Bekasi, 2020)
In general, a computer program will execute instructions serially. These instructions will be run on the CPU or referred to as serial computing. But when computing is run in large numbers, the time required by serial computing becomes very long. Therefore, we need another computation that can streamline data processing time such as parallel computing. Parallel computing can be done on GPUs (Graphical Processing Units) that are run with the help of toolkits such as CUDA (Computer Unified Device Architecture) and OpenCL (Open Computing Language). CUDA can only be run on NVIDIA graphics cards, while OpenCL can be run on all types of graphics cards. This research will compare the performance of parallel computing time between CUDA and OpenCL tested on uncompressed digital images. The digital image tested has several different sizes. The results of the study are expected to be a reference for digital image processing methods.